Peningkatan Keterampilam Membaca Aksara Jawa dengan Menerapkan Metode Quantum Learning Berbantu Media Karawa pada Siswa Sekolah Dasar - Lestari, Nunung; Fardani, Much Arsyad; Kironoratri, Lintang (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2024)
The background to this reseach is the low level of students Javanese script reading skills due to the lack of variety in the learning models and media used. This research aims to improve Javanese script reading skills using the Quantum Learning method assisted by Karawa media in elementary school students. This type of research is Classroom Action Research which consists of cycle I and cycle II. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The subjects of this research were 11 class III students at SDN 1 Purwogondo. The data collection techniques used are observation, interviews, tests and documentation. Data analysis techniques use quantitative and qualitative data. The result of this research show that Javanese script reading skills in the first cycle were 5 students who completed it by obtaining classical completeness of 45%, then the number of studens who completed it increased by 9 students with classical completeness of 82% in the second cycle. An increase in learning by implementing the quantum learning method assisted by Karawa media can help students improve their Javanese script reading skills.